Facile One-Step Preparation and Characterization of Graphene Quantum Dots Suspension via Electrochemical Exfoliation - Danial, Wan Hazman; Farouzy, Bashariah; Abdullah, Mundzir; Abdul Majid, Zaiton (Malaysian Institute of Chemistry, 2021)
This study reports on the production of graphene quantum dots (GQDs) suspension using a simple electrochemical setup which involved an electrolyte solution, consisting of citric acid and sodium hydroxide (NaOH) mixture, and pristine graphite rods for the electrode without any heating treatment (calcination), thus avoiding any high energy consumption. The balanced reaction mixture of citric acid and NaOH was used to investigate the effects of reaction time and voltage used towards the production of GQDs. UV-Vis spectroscopy analysis revealed significant UV absorption around 240-255 nm which depicted π→π∗transition of aromatic sp2 C-C bonds while FTIR analysis showed the significant C=C stretching band around 1635 cm-1 attributed by the aromatic ring. The exfoliation of the GQDs was increased as the concentration of NaOH in the electrolyte, time taken and voltage were increased. The optimum GQDs suspension can be obtained using a balanced ratio of citric acid and NaOH with a voltage of 10 V for 2 hours reaction time. TEM analysis confirmed the presence of the GQDs obtained with an average size of ∼5 nm for the optimum GQDs suspension. The exfoliation of GQDs via the electrochemical technique may pave the way towards upscale and sustainable production of the nanomaterial